A Note on Maximum Weight Independent Set in Outer-rectangle Graph - Piliposyan, Eduard T. (Mathematical Problems of Computer Science, 2021)
An outer-rectangle graph is the intersection graph of rectangles lying inside a rectangular box and having exactly one edge on the boundary of the box. We present a polynomial-time algorithm for the problem of computing a maximum weight independent set in 2-side outer-rectangle graphs where any two rectangles lying on same edge of box do not intersect.